The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41467-020-18371-2
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring π-conjugation and vibrational modes to steer on-surface synthesis of pentalene-bridged ladder polymers

Abstract: The development of synthetic strategies to engineer π-conjugated polymers is of paramount importance in modern chemistry and materials science. Here we introduce a synthetic protocol based on the search for specific vibrational modes through an appropriate tailoring of the π-conjugation of the precursors, in order to increase the attempt frequency of a chemical reaction. First, we design a 1D π-conjugated polymer on Au(111), which is based on bisanthene monomers linked by cumulene bridges that tune specific vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 61 publications
1
31
0
1
Order By: Relevance
“…[127] In 2020, de la Torre et al synthesized pentalene-bridged bisanthene on a gold surface and monitored the reaction by STM and AFM (Figure 19). [128] The on-surface polymerization led to a maximum length of twelve repeating units, with two isomers equally probable. Spatially resolved electronic measurements revealed that the polymer had a valence band at À 0.6 eV and a conduction band at 0.5 eV, resulting in a low band gap of ~1.1 eV.…”
Section: Pentalenementioning
confidence: 99%
See 1 more Smart Citation
“…[127] In 2020, de la Torre et al synthesized pentalene-bridged bisanthene on a gold surface and monitored the reaction by STM and AFM (Figure 19). [128] The on-surface polymerization led to a maximum length of twelve repeating units, with two isomers equally probable. Spatially resolved electronic measurements revealed that the polymer had a valence band at À 0.6 eV and a conduction band at 0.5 eV, resulting in a low band gap of ~1.1 eV.…”
Section: Pentalenementioning
confidence: 99%
“…Polymer 132 was deposited on an Au(111) surface, and upon annealing, polymers containing fused dibenzopentalene units were formed (one isomer is shown). nc-AFM/STM images adapted from Ref [128],. Copyright (2020), with permission from Springer Nature Limited.…”
mentioning
confidence: 99%
“…Upon further annealing at 650 K, the 117 wire underwent two-fold cyclization reaction between adjacent bisanthene moieties and obtained a long pentalenebridged conjugated ladder polymer. [103] In 2020, they further extended this chemistry to build one-dimensional cumulenelike polymers 118 based on [5,2]PA units. [104] Towards the synthesis of 118, on-surface reactions of 13,13'bis(dibromomethylene)-13H,13'H-6,6'-bipentacenylidene precursor (41) was performed on Au(111) under UHV conditions (Figure 27g).…”
Section: Pa-based Graphene Nanoribbons and Pa-bridged Cumulene Polymersmentioning
confidence: 99%
“…Tatsächlich wurde kürzlich gezeigt, dass solche mobilen Adatome, die bei hohen Temperaturen häufig auf Metalloberflächen vorhanden sind, wichtige Reaktionsschritte wie die tautomere Dehydrierung von Keto-Enol, [40] und die C-C-Kopplung fördern. [41][42][43] Daher haben wir QM/MM [44] -Berechnungen der freien Energie mit der WHAM-Methode [45] durchgeführt, um diese Hypothese zu untersuchen. Tatsächlich zeigen die QM/MM-Simulationen eine erhebliche Verringerung der Aktivierungsenergien um � 60 kcal mol À 1 .…”
Section: Die Dehydrierende Kupplungsreaktion Zweier Arenringeunclassified